Design and FEM Analysis of Hydraulic Tire Curing Press - V. Jaipal, R. Maheshgoud (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This project includes structural construction of hydraulic tire curing press, mold assembly, and also hydraulic power pack to operate machine in automotive way. In this project work all these three main sub-assemblies are clubbed together and with the proper hydraulic load’s application on the machine along with self-loads and gravitational forces. Then we start the structural analysis over the frame of hydraulic tire curing press during opening and closing of top platen to the bottom platen, in order to close the mold with different closing times and speeds with the help of hydraulic power pack.Main aim of this project is to observe the stress distribution and deflections on structure at various loads,with the help of static and model analysis on the main frame. Then by verifying the results we canestimate the stability of machine main frame to with stand for working, so that we can rectify the sudden breakdowns of machines and that affects the production loses.Modeling is done by using solid works 2016.and for analysis we used ansys16.0 software.